Replacement of corn bran by Astrocaryum aculeatum G. Mey. pie flour in the diets of Colossoma macropomum - XAVIER, DÉBORA; Xavier, Débora Tatyane Oliveira; Soares, Priscila Pinho; Rossetto, Janaina Fernanda; Souza, Herivelto Beck de; Brisqueleal, Jean Carlos Pianta; Souza, Raimundo Aderson Lobão de (Pubvet, 2019)
The objective of this research was to evaluate the effect of the substitution of corn bran (Zea mays L.) on the pulp meal of tucumã (Astrocaryum aculeatum G. Mey.) In diets for juvenile tambaqui (Colossoma macropomum). The experiment was developed at the Federal Institute of Education, Science and Technology of Pará (IFPA) Campus Castanhal, with duration of 45 days of cultivation. The samples, with a mean initial weight of 7.8 ± 1.151 g were randomly distributed in polyethylene boxes with a capacity of 210 liters in five treatments and three replicates each, with a completely randomized design, totaling 90 animals per treatment, 30 individuals per experimental unit. Diets were offered at a rate of 5% of the total biomass, six times a day. Biometrics were performed biweekly. Water analyzes were collected weekly, while siphoning occurred daily. At the end of the experiment, animal performance parameters of the animals were evaluated as: Weight gain (GP); Feed consumption (CR); apparent feed conversion (CAA); Specific growth rate (TCE); Protein efficiency rate (TEP) and Survival rate (S). In the experimental conditions used, it can be stated that maize meal may be substituted by up to 25% of tucumã pie meal in diets for juveniles of tambaquis in water tank, without compromising performance variables. In this way, its potential to compose diets with good nutritional quality for frugivorous fish is evidenced.
Keywords: alternative energy; nutrition; fish farming